Ipet A Training Model for The Teaching of Education Environmental In Basic Education (Global Journal of Human-Social Science, 2023)
In Colombia the environmental dimension in the school is circumscribed to the transversal model however Teachers in particular of basic education do not have adequate updated and broad conceptual frameworks that allow them to generate necessary actions against the objectives of environmental education and the training of citizens capable of making decisions about the environmental situations of the territories that inhabit Teachers generally have reduced visions of the environment and environmental education and their actions are activists with little reflection or leading to real transformations This research advocates giving importance to teacher training so that the teaching of environmental education at school is reflected and new models are promoted The research is qualitative transformative and presents the case of 6 natural science teachers from Ibagu Tolima in Colombia It allows as results after an academic year of permanent formative and reflective work the transformation of the teaching models of these teachers The formative processes and reflection on the practice itself are concluded allowing substantial improvements in the teaching models of environmental education in basic education
Keywords: teacher training; environmental education; teaching models